Growth Performance Of The West African Dwarf Sheep (Djallonké) At The National Sheep Breeding Station-Ejura - Danso-Mireku, E. (University Of Ghana, 2020)
Data on 625 production records collected between 2000 and 2010 on Djallonke sheep at the National Sheep Breeding Station, Ejura in the Ashanti region was used to investigate the effects of non-genetic factors such as season of birth, year of birth, type of birth and sex of lamb on growth parameters such as birth weight, weaning weight, yearling weight, pre-weaning growth rate and post-weaning growth rate. The lambs generally weighed 2.07kg at birth, grew at 64.10 grammes per day to attain an average weaning weight of 9.77kg at 120 days. Thereafter, the lambs gained an average of 29.60g daily to reach a yearling weight of 17.02kg. On the whole, sex of lamb was the only non-genetic factor that did not significantly (p > 0.05) affect any of the traits whilst year of birth was the only factor that was found to have significantly (p < 0.05) affected all the traits of interest in this study. However, type of birth did not significantly (p > 0.05) affect the birth and yearling weight of lambs but significantly (p < 0.05) affected pre and post-weaning daily gain together with the weight of the lambs at 120-day weaning weight. Season of birth significantly affected the pre-weaning daily gain and weaning weight but did not affect the lamb birth weight, post weaning daily gain and yearling weight.
M.A. Animal Science
Keywords: Growth Performance; West African Dwarf Sheep; Sheep Breeding; Ejura